Structure of the velocity distribution of sheath-accelerated secondary electrons in an asymmetric RF-dc discharge. (13th August 2015) - Khrabrov, Alexander V; Kaganovich, Igor D; Ventzek, Peter L G; Ranjan, Alok; Chen, Lee
Abstract: Low-pressure capacitively-coupled discharges with additional dc bias applied to a separate electrode are utilized in plasma-assisted etching for semiconductor device manufacturing. Measurements of the electron velocity distribution function (EVDF) of the flux impinging on the wafer, as well as in the plasma bulk, show a thermal population and additional peaks within a broad range of energies. That range extends from the thermal level up to the value for the 'ballistic' peak, corresponding to the bias potential. The non-thermal electron flux has been correlated to alleviating the electron shading effect and providing etch-resistance properties to masking photoresist layers. 'Middle-energy peak electrons' at energies of several hundred eV may provide an additional sustaining mechanism for the discharge. These features in the electron velocity (or energy) distribution functions are possibly caused by secondary electrons emitted from the electrodes and interacting with two high-voltage sheaths: a stationary sheath at the dc electrode and an oscillating self-biased sheath at the powered electrode. Since at those energies the mean free path for large-angle scattering (momentum relaxation length) is comparable to, or exceeds the size of the discharge gap, these 'ballistic' electrons will not be fully scattered by the background gas as they traverse the inter-electrode space. We have performed test-particle simulations in which the features in the EVDF of electrons impacting the RF electrode are fully resolved at all energies. An analytical model has been developed to predict existence of peaked and step-like structures in the EVDF. Those features can be explained by analyzing the kinematics of electron trajectories in the discharge gap. Step-like structures in the EVDF near the powered electrode appear due to accumulation of electrons emitted from the dc electrode within a portion of the RF cycle, and their subsequent release. Trapping occurs when the RF sheath voltage exceeds the applied bias, and is decreasing. The secondary electrons originating from the dc-biased surface also form a peak near the energy equal to the bias potential. Additional peaks, at lower energies, are formed by the electrons emitted from the RF electrode and eventually escaping to it. The latter can be grouped according to the number of bounces between the sheaths during their residence time in the discharge. Each of such groups may give rise to an individual peak in the distribution. The trap-and-release theory developed in this paper provides a convincing explanation for the observations of the ballistic and 'middle energy peak' electrons detected in experiments.